High‐Resolution Water Footprints of Production of the United States. Issue 3 (26th March 2018) - Marston, Landon; Ao, Yufei; Konar, Megan; Mekonnen, Mesfin M.; Hoekstra, Arjen Y.
Abstract: The United States is the largest producer of goods and services in the world. Rainfall, surface water supplies, and groundwater aquifers represent a fundamental input to economic production. Despite the importance of water resources to economic activity, we do not have consistent information on water use for specific locations and economic sectors. A national, spatially detailed database of water use by sector would provide insight into U.S. utilization and dependence on water resources for economic production. To this end, we calculate the water footprint of over 500 food, energy, mining, services, and manufacturing industries and goods produced in the United States. To do this, we employ a data intensive approach that integrates water footprint and input‐output techniques into a novel methodological framework. This approach enables us to present the most detailed and comprehensive water footprint analysis of any country to date. This study broadly contributes to our understanding of water in the U.S. economy, enables supply chain managers to assess direct and indirect water dependencies, and provides opportunities to reduce water use through benchmarking. In fact, we find that 94% of U.S. industries could reduce their total water footprint more by sourcing from more water‐efficient suppliers in their supply chain than they could by converting their own operations to be more water‐efficient. Key Points: We present the most detailed and comprehensive water footprints of production of any country to date Significant variability is evident in water footprints of production between locations and economic sectors Sourcing from water‐efficient suppliers (indirect use) reduces water footprints more than changes to direct use